An insight into the role of the N-terminal domain of Salmonella CobB in oligomerization and Zn2+ mediated inhibition of the deacetylase activity - Beura, Shibangini; Pritam, Pulak; Dhal, Ajit Kumar; Jana, Arindam; Dash, Aiswarya; Mohanty, Pritisundar; Panda, Alok Kumar; Modak, Rahul (Frontiers in Molecular Biosciences, 2024)
Prokaryotic deacetylases are classified into nicotinamide adenine dinucleotide (NAD+)-dependent sirtuins and Zn2+-dependent deacetylases. NAD+ is a coenzyme for redox reactions, thus serving as an essential component for energy metabolism. The NAD+-dependent deacetylase domain is quite conserved and well characterized across bacterial species like CobB in Escherichia coli and Salmonella, Rv1151c in Mycobacterium, and SirtN in Bacillus subtilis. E. coli CobB is the only bacterial deacetylase with a known crystal structure (PDB ID: 1S5P), which has 91% sequence similarity with Salmonella CobB (SeCobB). Salmonella encodes two CobB isoforms, SeCobBS and SeCobBL, with a difference of 37 amino acids in its N-terminal domain (NTD). The hydrophobic nature of NTD leads to the stable oligomerization of SeCobBL. The homology modeling-based predicted structure of SeCobB showed the presence of a zinc-binding motif of unknown function. Tryptophan fluorescence quenching induced by ZnCl2 showed that Zn2+ has a weak interaction with SeCobBS but higher binding affinity toward SeCobBL, which clearly demonstrated the crucial role of NTD in Zn2+ binding. In the presence of Zn2+, both isoforms had significantly reduced thermal stability, and a greater effect was observed on SeCobBL. Dynamic light scattering (DLS) studies reflected a ninefold increase in the scattering intensity of SeCobBL upon ZnCl2 addition in contrast to an ∼onefold change in the case of SeCobBS, indicating that the Zn2+ interaction leads to the formation of large particles of SeCobBL. An in vitro lysine deacetylase assay showed that SeCobB deacetylated mammalian histones, which can be inhibited in the presence of 0.25–1.00 mM ZnCl2. Taken together, our data conclusively showed that Zn2+ strongly binds to SeCobBL through the NTD that drastically alters its stability, oligomeric status, and enzymatic activity in vitro.